Comparative Morphology of the Larynx, Trachea and Lungs of Asian Elephant (Elephas maximus indicus) and Domestic Animals - Rajani, C.V. (Indian Journal of Veterinary Anatomy, 2019)
Respiratory system of elephant possesses many salient characteristics such as trunk, long nasal passages and absence of typical pleural cavity. The study was conducted on larynx, trachea, and lungs collected from Asian elephants, cattle, horse, pig and dog. Larynx possessed all the four major cartilages viz., epiglottis, thyroid, arytenoid and cricoid. The apex of epiglottis had a rounded margin in elephant, cattle, and pig but pointed in horse, and dog. Elephant and horse lacked a laryngeal prominence and presented a deep caudal thyroid notch. However, laryngeal prominence was prominent in cattle, and pig. Elephant larynx had blunt corniculate processes, ventricular and vocal folds, a median laryngeal saccule and two lateral laryngeal ventricles. Although elephant possessed both parietal and visceral pleura, a pleural cavity between the layers was absent.